Exercise Dependence and Perfectionism: a Novel Issue in Sport Environment? - P. Venuti; C. Furlanello; A.M. Peirò; T. Zandonai (Emerging Trends in Drugs, Addictions, and Health)
Introduction: Exercise dependence (ED) can be defined as a maladaptive pattern of excessive exercise that manifests in physiological and psychological and cognitive symptoms (Biggs et al 2021). Moreover, perfectionism is a multidimensional personality disposition characterized by setting exacting standards, striving for perfection and harsh criticism (Hill et al 2015). The aim of our study was to investigate the correlation between these two variables. Methods: The ED level of the participants was assessed using the Exercise Dependence Scale-Revised (EDS-R) while the perfectionism we used the Multidimensional Inventory of Perfectionism in Sport” (MIPS). A specific survey online was performed. Correlations between variables were calculated using Pearson's r for normal distributed data and Spearman's rho for non-normal distributed data. For supplements consume we used a contingence analysis (Pearson's Chisquared test, 3 × 2). Results: On a sample of 341 Spanish athletes (mean age 25.6 years (SD 8.3), 57% men, 43% women), 6% were at risk of dependence (AR), 57% were non-dependent symptomatic (NDS) while 37% were non-dependent asymptomatic. EDS-R score was positively correlated with MIPS score (r=0.3692, p<0.001) and we found a higher use of supplements in AR (50%) vs NDS (26%) participants (p=0.029). Conclusions: Exercise dependence appears to be positively associated with perfectionism and supplements use. However, these relationships should be examined in future research to confirm this trend, and possibly identify a risk stratification model.